2015
DOI: 10.1371/journal.pone.0121562
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Sensorimotor Activity by Controlling Virtual Objects with Gaze

Abstract: This fMRI work studies brain activity of healthy volunteers who manipulated a virtual object in the context of a digital game by applying two different control methods: using their right hand or using their gaze. The results show extended activations in sensorimotor areas, not only when participants played in the traditional way (using their hand) but also when they used their gaze to control the virtual object. Furthermore, with the exception of the primary motor cortex, regional motor activity was similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…For example, if the direct matching hypothesis is accurate, our eye movements should be approximately the same whether we are observing or performing an action. For example, in one recent study regional motor activity was shown to be highly similar irrespective of whether an arm or an eye was being utilized to control a virtual object ( Modroño et al, 2015 ). It is unlikely, however, that when performing actions we employ PG in the way operationalised herein (i.e., looking at our own hand and then predictively at the object we are reaching to grasp).…”
Section: Discussionmentioning
confidence: 99%
“…For example, if the direct matching hypothesis is accurate, our eye movements should be approximately the same whether we are observing or performing an action. For example, in one recent study regional motor activity was shown to be highly similar irrespective of whether an arm or an eye was being utilized to control a virtual object ( Modroño et al, 2015 ). It is unlikely, however, that when performing actions we employ PG in the way operationalised herein (i.e., looking at our own hand and then predictively at the object we are reaching to grasp).…”
Section: Discussionmentioning
confidence: 99%
“…A statistical parametric map resulting from this contrast was displayed on the surface and on three selected axial slices of a MNI single‐subject T1 image (Figure ). The results revealed activations in cortical and noncortical regions typically involved in visuomotor tasks (Modroño et al, ; Modroño, Navarrete, Rodriguez‐Hernandez, & Gonzalez‐Mora, ), including the supplementary motor area, the premotor cortex, the primary motor cortex, the basal ganglia, the thalamus, parieto‐occipital regions and the cerebellum. Activations were found in the left (but not in the right) primary motor cortex, which is consistent with the fact that the task was performed with the right hand.…”
Section: Resultsmentioning
confidence: 86%
“…These regions are: the left dorsal premotor cortex (dPMC), the supplementary motor area (SMA), the primary motor cortex (M1), the putamen, and the cerebellum (Hardwick et al, ). Thus, at the cortical level, we predict activations in the left dPMC and in the SMA (during the learning period, the sensorimotor task is controlled with the eye and presumably the M1 is not involved [Modroño et al, ], thus, the M1 will not initially be proposed as a candidate to be activated at transfer). At the subcortical level, we predict activations in the putamen and the cerebellum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, VR and AOT modulate the MNS to achieve an improvement in the functional condition of patients. In this respect, some studies have shown the presence of an intense MNS activity during VR tasks [51,52].…”
Section: Aot and Virtual Reality: Two Heads Of The Same Coinmentioning
confidence: 99%